2015
DOI: 10.3390/molecules201219864
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Breast Cancer by Dietary Polyphenols

Abstract: Abstract:The review will discuss in detail the effects of polyphenols on breast cancer, including both the advantages and disadvantages of the applications of these natural compounds. First, we focus on the characterization of the main classes of polyphenols and then on in vitro and in vivo experiments carried out in breast cancer models. Since the therapeutic effects of the administration of a single type of polyphenol might be limited because of the reduced bioavailability of these drugs, investigations on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
80
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 279 publications
(369 reference statements)
2
80
0
2
Order By: Relevance
“…Also in agreement with the observation that genes involved in mitosis and cell cycle are induced by GSGME is that several genes encoding histone proteins, which play a role for nucleosome assembly and thus affect chromatin structure, were up-regulated by GSGME. Although it is difficult to estimate the precise biological implication of an up-regulation of genes involved in mitosis or cell cycle regulation by GSGME in the context of early-lactating dairy cows, this effect might be explained, at least in part, by the well-described effects of different polyphenolic compounds contained in GSGME on cell cycle regulation and apoptosis, effects that are made responsible for the anti-cancer activities of many polyphenols [77]. For instance, quercetin [78], curcurmin [79], ellagic acid [80], epigallocatechin-3-gallate [81] and resveratrol [82] were found to induce the critical cell cycle regulator p53 and, subsequently, cell cycle arrest and apoptosis in different cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also in agreement with the observation that genes involved in mitosis and cell cycle are induced by GSGME is that several genes encoding histone proteins, which play a role for nucleosome assembly and thus affect chromatin structure, were up-regulated by GSGME. Although it is difficult to estimate the precise biological implication of an up-regulation of genes involved in mitosis or cell cycle regulation by GSGME in the context of early-lactating dairy cows, this effect might be explained, at least in part, by the well-described effects of different polyphenolic compounds contained in GSGME on cell cycle regulation and apoptosis, effects that are made responsible for the anti-cancer activities of many polyphenols [77]. For instance, quercetin [78], curcurmin [79], ellagic acid [80], epigallocatechin-3-gallate [81] and resveratrol [82] were found to induce the critical cell cycle regulator p53 and, subsequently, cell cycle arrest and apoptosis in different cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…17 Numerous studies have evaluated the antioxidant activity and beneficial biological effects of propolis. 2,8,9,13,16 Propolis shows antioxidant properties because of its free radical scavenging capacity, which aroused the need of conducting further researches about them in many areas.…”
mentioning
confidence: 99%
“…12 Since these compounds are secondary plant metabolites, they cannot be synthesized by humans and so they are forming a significant part of human diet. 13 Flavonoids display their biological activities by bonding heavy metal ions and biological polymers, by catalyzing electron transport and scavenging free radicals. 13,14 Recent studies have showed that flavonoids protect DNA and other components of the cell from oxidative damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Moreover, a large body of literature is available on the efficacy of flavonoids with regard to chemoprevention and chemotherapy. 20,[22][23][24] High cost, toxic nature and rapid development of resistance have become synonymous with conventional cancer treatment. 25,26 As such, there is an overwhelming need to invest in research that aims to identify new lead compounds that may address these challenges.…”
mentioning
confidence: 99%